1924
DOI: 10.1007/bf03184837
|View full text |Cite
|
Sign up to set email alerts
|

Studien zur Berührungselektrizität: Die Ladung von Metallen gegen Dielektrika

Abstract: 1. Der Voltaeffekt und die Aufladung der Dielektrika im Hochvakuum. 2. Ladung von Glas und Quarz gegen andere Dielektrika. 3.~Ietalle gegen vcrschiedene Dielektrika. 4. Die Umkehrkonzentration bei Amalgamen. 5. Die Grolle der Aufladung und ihre Abhangigkeit von der Hohe des Vakuums. 6. Eine Methode, welche die Untersuchung der beruhrungselektrischen Erscheinungen am Diamant ermoglicht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1927
1927
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The rate of gain of charge during rolling seems to be quite well understood (Peterson 1954, Wagner 1956, Ruckdeschel and Hunter 1975 but the factors controlling the magnitude and sign of charge transfer are not. It has been reported that different kinds of glass behave rather similarly (crown and flint, Harper (1967); lead and soda, Shaw and Jex (1928)) but quite differently from silica and quartz which are much more negative (Coehn and Curs 1924, Coehn and Lotz 1921, Schnurmann 1941. Recent carefully controlled experiments indicate that charge transfer from metals to glass may be correlated with the metal workfunction, metals with large workfunctions transferring more positive charge (Davies 1967, Inculet andWituschek 1967); this dependence on workfunction led Davies to propose that the charge transfer was such as to equalise the chemical potential of electrons in the two contacting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of gain of charge during rolling seems to be quite well understood (Peterson 1954, Wagner 1956, Ruckdeschel and Hunter 1975 but the factors controlling the magnitude and sign of charge transfer are not. It has been reported that different kinds of glass behave rather similarly (crown and flint, Harper (1967); lead and soda, Shaw and Jex (1928)) but quite differently from silica and quartz which are much more negative (Coehn and Curs 1924, Coehn and Lotz 1921, Schnurmann 1941. Recent carefully controlled experiments indicate that charge transfer from metals to glass may be correlated with the metal workfunction, metals with large workfunctions transferring more positive charge (Davies 1967, Inculet andWituschek 1967); this dependence on workfunction led Davies to propose that the charge transfer was such as to equalise the chemical potential of electrons in the two contacting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ruckdeschel andHunter (1975, 1977) have interpreted their measurements of charge transfer between glass and oxidised A1 in this way, and they have further suggested that the amount of charge may be limited by thermally activated back-transfer of ions during separation of the surfaces. Coehn and Curs (1924) attempted to account for the different behaviour of quartz and glass (see above) by invoking two mechanisms: electron transfer and the migration of metal ions into the insulator. They supposed the second mechanism to be much more effective in glass, because of its more open structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is the reaction of chlorine atoms with hydrogen molecules. Coehn and Jung (10) have established that in very dry hydrogen-chlorine mixtures no measurable reaction occurs on illumination, although it is known that chlorine atoms are produced. To account for the lack of reaction, the reaction rate of chlorine atoms with hydrogen molecules must be so slow that an activation energy well in excess of 10,000 cal.…”
Section: Br2mentioning
confidence: 99%
“…With respect to the photochemical formation of the hydrogen chloride by the absorption of light by chlorine it is necessary to mention that the absorption of light in the continuous region and beginning with 3000 Á. 33 has been found to be effective when the gases are dry. In the presence of traces of water vapor wave lengths in the region of band absorption in the visible are also effective.…”
Section: Cont Ultraviolet12mentioning
confidence: 99%